KADAR KOLESTEROL, UREA, KREATININ DARAH DAN KOLESTEROL TELUR AYAM SENTUL DENGAN PENAMBAHAN EKSTRAK BUAH MENGKUDU YANG DISUPLEMENTASI Cu DAN Zn - Nai Nurazizah; Abidah Ishma Nabila; Lovita Adriani; Tuti Widjastuti; Diding Latipudin (Jurnal Nutrisi Ternak Tropis dan Ilmu Pakan, 2020)
The research was conducted to know the effect of noni fruit extract supplemented by Cu and Zn on blood cholesterol and  egg yolk cholesterol, creatinin, and blood urea nitrogen of sentul chicken. The research was done from August until October 2019. Samples test was held in Physiology and Biochemistry Laboratory, Animal Husbandry Faculty, Padjadjaran University, Sumedang. The methods used experimental with a Completely Randomized Design (CRD) and the effect of treatment using Analysis of  Varience (ANOVA) followed by Orthogonal Polynomial. The treatment consisted of five kind with five repetitions, those are to =  without adding noni fruit extract and  Cu, Zn , t1= Ration + 60 mg/kg extract noni fruit suplemented Cu 0,06 mg and Zn 1,5 mg, t2= Ration+ 180 mg/kg extract fruit noni suplemented Cu 0,18 mg and Zn 3,0 m, t3= Ration + 240 mg/kg extract fruit noni suplemented Cu 0,24 mg and Zn 4,5 mg, t4= Ration + 360 mg/kg extract fruit noni suplemented Cu 0,36 and Zn 6,0 mg. The result showed that the effect of giving 360 mg/kg noni extract suplemented Cu 0,36 and Zn 6,0 mg was significant effect  decreasing blood cholesterol levet but non significant  decreasing egg yolk cholesterol, creatinin, and blood urea nitrogen levels of Sentul Chicken. Keywords:  noni fruit extract, cholesterol, urea, creatinin, blood, egg yolk              cholesterol, sentul chicken, mineral Cu and ZnThe research was conducted to know the effect of noni fruit extract supplemented by Cu and Zn on blood cholesterol and  egg yolk cholesterol, creatinin, and blood urea nitrogen of sentul chicken. The research was done from August until October 2019. Samples test was held in Physiology and Biochemistry Laboratory, Animal Husbandry Faculty, Padjadjaran University, Sumedang. The methods used experimental with a Completely Randomized Design (CRD) and the effect of treatment using Analysis of  Varience (ANOVA) followed by Orthogonal Polynomial. The treatment consisted of five kind with five repetitions, those are to =  without adding noni fruit extract and  Cu, Zn , t1= Ration + 60 mg/kg extract noni fruit suplemented Cu 0,06 mg and Zn 1,5 mg, t2= Ration+ 180 mg/kg extract fruit noni suplemented Cu 0,18 mg and Zn 3,0 m, t3= Ration + 240 mg/kg extract fruit noni suplemented Cu 0,24 mg and Zn 4,5 mg, t4= Ration + 360 mg/kg extract fruit noni suplemented Cu 0,36 and Zn 6,0 mg. The result showed that the effect of giving 360 mg/kg noni extract suplemented Cu 0,36 and Zn 6,0 mg was significant effect  decreasing blood cholesterol levet but non significant  decreasing egg yolk cholesterol, creatinin, and blood urea nitrogen levels of Sentul Chicken. Keywords:  noni fruit extract, cholesterol, urea, creatinin, blood, egg yolk              cholesterol, sentul chicken, mineral Cu and Zn